Characterization of Bioactive Compounds in Foods and Plants Using Advanced Analytical Techniques - Russo, Marina; Cacciola, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Since the 1990s, food chemistry opened a new chapter in foods and plants investigation. An increasing attention to secondary metabolites and micro-constituents of nutraceutical interest present in foods has been noticed, supporting previous studies on macronutrient composition. Thanks to positive scientific opinions on the presence of bioactive molecules in plants and foods, the previous vision of exploring foods exclusively from a "caloric" point of view has been changed to looking at foodstuffs as having positive effects on human health.This book focuses on the optimization and validation of advanced analytical methodologies dedicated to the characterization and valorization of foods and plants containing bioactive molecules. Qualitative and quantitative characterization, food security, traceability, and innovation in the field of nutraceutical and functional nutrition will be of particular interest in order to stimulate a dialogue on correct nutrition concepts in a constantly changing cultural, technological, and climate context.